Autocrine mechanisms of cancer chemoresistance. (June 2018) - Butera, Giovanna; Pacchiana, Raffaella; Donadelli, Massimo
Abstract: An ever-increasing number of studies highlight the role of cancer secretome in the modification of tumour microenvironment and in the acquisition of cancer cell resistance to therapeutic drugs. The knowledge of the mechanisms underlying the relationship between cancer cell-secreted factors and chemoresistance is becoming fundamental for the identification of novel anticancer therapeutic strategies overcoming drug resistance and novel prognostic secreted biomarkers. In this review, we summarize the novel findings concerning the regulation of secreted molecules by cancer cells compromising drug sensitivity. In particular, we highlight data from available literature describing the involvement of cancer cell-secreted molecules determining chemoresistance in an autocrine manner, including: i) growth factors; ii) glycoproteins; iii) inflammatory cytokines; iv) enzymes and chaperones; and v) tumor-derived exosomes.